Economical security of "Rosenergoatom Concern" OJSC: elaboration of staff training and development section of balanced scorecard ("Journal "U". Economy. Management. Finance.", 2017)
In the article the author develops a balanced scorecard staff development section of "Rosenergoatom Concern" OJSC. Balanced scorecard is considered in the article as an instrument of controlling, planning and monitoring of economical security maintenance through human resource management system.
Keywords: staff management; staff flow; economical security; balanced scorecard; nuclear power plant; couching; staff development